Representasi Kehidupan Masyarakat dalam Novel Si Anak Badai Karya Tere Liye (Kajian Sosiologi Sastra) - Ahmad, Putri Anggraini T; Baruadi, Moh. Karmin; Lantowa, Ja'far (Jambura Journal of Linguistics and Literature, 2023)
This study aims to describe the representation of people's lives in Tere Liye's novel "The Child of the Storm" by using the theory of sociology of literature. The approach used is descriptive qualitative, with the data source in the form of the novel. Data collection methods involve techniques of reading, paying attention, noting, and coding. The results of the study show six important elements in the representation of people's lives in this novel. First, there is a representation of the environmental conditions of the community facing social problems. Second, the friendship of the children in Manowa village is an important element in representing community life. Third, courage and enthusiasm are shown in this novel. Fourth, cooperation becomes the dominant aspect in people's lives, where they always work together in everything. Fifth, responsibility is reflected in the roles of parents and children in Manowa village. Finally, the representation of the livelihoods of the Manowa people who mostly live in floating villages is also found in this study.